Examining Argument Elements and Logical Fallacies of English Education Students in Oral Discussion - Selamat Husni Hasibuan; Y Yusriati; Imelda Darmayanti Manurung (Tell : Teaching of English Language and Literature Journal, 2020)
This study aims to report on the argument elements and logical fallacies performed by English education students. This study is framed within a descriptive qualitative study in that it interprets the ways students of English education deliver their arguments. The data were collected through observation, recording and in-depth interviews on the objects studied. The findings of this study showed that the studentsâ€™ ability to present logical arguments varies with the dominant label in the â€œnon-standard argumentâ€ category. In regard to the logical fallacy, hasty generalization becomes the most general logical fallacy found in studentsâ€™ arguments, followed by the appeal to pity, the appeal to fear, the questionable statistics, the slippery slope, the appeal to the bandwagon, the circular reasoning, the pointing to another wrong, and the personal attack. Based on the interview, lack of understanding of arguments and logical fallacies, limited vocabularies, as well as nervousness are identified as the possible causes of these phenomenons. Finally, it is suggested that students should be given exposures on how to structurize the logical arguments and avoid logical fallacies.